BATIK DAN TENUN : CERMINAN BUDAYA MELAYU BAGIAN DARI EKONOMI DAN INDUSTRI KREATIF DI KOTA JAMBI - Siti Heidi Karmela (Universitas Batanghari Jambi, 2015)
The diversity of ethnicity ( race or ethnicity ) in Jambi can be seen from the diverse cultures that produced , one of which is batik and tenun produced by Jambi Malay . The creativity of local people , especially craftsmen in the processing and marketing of new products of the craft , it can help increase their income . This indicates that the sector is no longer just a domestic industry and small industry , but has grown into a medium-sized industry , subsequent to the process of diversification .If at first centers of craft production only in the area of Jambi seberang ( sekoja ) alone , but eventually emerging centers of new production in the area of Jambi kota (Jambi city) indicating that the craft sector is positive implications economically good for the craftsmen , laborers , entrepreneurs , and for the improvement of other sectors such as the tourism industry in the city of Jambi .Keywords : craft , batik , tenun , Malay , Jambi